Treatment of postoperative lymphatic leakage applying transpedal lymphangiography: experience in 355 consecutive patients - Pan, Feng; Richter, Götz Martin; Do, Thuy; Kauczor, Hans-Ulrich; Klotz, Rosa; Hackert, Thilo; Loos, Martin; Sommer, Christof-Matthias (RöFo, 2022)
Purpose Report of experience from a single institution in treating postoperative lymphatic leakage (PLL) applying conventional transpedal lymphangiography (TL). Materials and Methods 453 patients with the initial diagnosis of PLL receiving TL between 03/1993 and 09/2018 were identified in the database. Only patients with confirmed PLL were included in the study. The technical success, safety, and treatment success of TL were evaluated. Independent predictors of TL treatment failure were examined using univariate and multivariate logistic regression analysis. Results 355 consecutive patients (218 men, 137 women; median age of 62 years) who underwent TL for PLL (e. g., chylothorax) after ineffective conservative treatment were included. The median time between causal surgery and TL was 27 days. The median technical success rate of TL was 88.5 %, with a median volume of Lipiodol of 10.0 ml. No complication of TL was recorded. Three groups were defined according to the different clinical courses: group A (41/355, 11.5 %) - TL with technical failure; group B (258/355, 72.7 %) - “therapeutic” TL alone with technical success; and group C (56/355, 15.8 %) - “diagnostic” TL with simultaneously invasive treatment (incl. surgical revision and percutaneous sclerotherapy). Treatment success rate and median time to treatment success were higher in group C than in group B, but without significant differences (64.3 % vs. 61.6 %, p = 0.710; six vs. five days, p = 0.065). Univariate and multivariate logistic regression analyses for group B confirmed drainage volume (> 500 ml/d) and Lipiodol extravasation as independent predictors of TL clinical failure (odds ratios [ORs] of 2.128 and 2.372 [p = 0.005 and p = 0.003, respectively]). Conclusion TL is technically reliable, safe, and effective in treating PLL. When conservative treatment fails, TL can be regarded as the next treatment option. Key Points: Citation Format
Gesehen am 07.07.2022